Implementation of Volunteer Roles in the Literacy Program at Rumah Pintar Punggur Cerdas, Sungai Kakap District - Amanda, Dea Tria; Imran, Imran; Wahyuni, Fauziah Sri; Syamsuri, Syamsuri; Imanulyaqin, Muhammad Nur (Universitas Tanjungpura, 2025)
This study aims to analyze the role of volunteers in the implementation of the literacy program at Rumah Pintar Punggur Cerdas, Sungai Kakap District, Kubu Raya Regency. The low literacy rate in Indonesia highlights the importance of community-based non-formal education, in which Rumah Pintar functions as a strategic learning center. Volunteers play a crucial role as facilitators, motivators, and innovators in ensuring the sustainability of the literacy program. This research employs a qualitative descriptive approach. Data were collected through observations, in-depth interviews, and documentation involving active volunteers and program organizers at Rumah Pintar Punggur Cerdas. The findings show that volunteers act as facilitators by assisting reading activities and creating an inclusive learning environment; as motivators by fostering reading interest and building emotional connections with participants; and as innovators through the use of media, technology, and creative ideas tailored to community needs. However, the implementation of these roles faces several challenges, such as the limited number of volunteers, inadequate facilities, and the lack of community support. These findings emphasize that volunteer involvement is a key factor in ensuring the sustainability and effectiveness of community-based literacy programs. This study is expected to provide theoretical contributions to the study of non-formal literacy education as well as practical insights for strengthening the role of volunteers in literacy initiatives.